1H NMR-metabolomics studies on acute toxicity effect of lead in adult zebrafish (Danio rerio) model - Chong, Siok Geok; Ismail, Intan Safinar; Chong, Chou Min; Mad Nasir, Nadiah; Saleh Hodin, Nur Atikah (Taylor & Francis, 2024)
Zebrafish (Danio rerio) is ideal for studying the effects of toxins like lead or plumbum (Pb) which persist in the environment and harm body systems when absorbed. Increasing Pb concentration could result in a higher mortality rate and alteration of behavior and metabolism. The present study evaluates the acute toxicity effect of Pb on metabolome and behavior in adult zebrafish. The zebrafish were exposed to various Pb concentrations ranging from 0 to 30 mg/L for different periods (24, 48, and 72 h) before the fish samples were subjected to Nuclear Magnetic Resonance (NMR)-multivariate data analysis (MVDA) with additional support from behavioral assessment. The behavior of zebrafish was significantly altered after Pb inducement and the differential metabolites increased in low (5 mg/L) while decreased in high (10 mg/L) Pb concentrations. An ideal Pb induction could be achieved by 5 mg/L concentration in 24 h, which induced significant metabolite changes without irreversible damage. Continuing research on the effects of lead toxicity is crucial to develop effective prevention and treatment strategies.